Floquet dynamical quantum phase transitions in transverse XY spin chains under periodic kickings - Luan, Li-Na; Zhang, Mei-Yu; Wang, Lin-Cheng (Chinese physics B, 2023)
Floquet dynamical quantum phase transitions (DQPTs), which are nonanalytic phenomena recuring periodically in time-periodic driven quantum many-body systems, have been widely studied in recent years. In this article, the Floquet DQPTs in transverse XY spin chains under the modulation of δ -function periodic kickings are investigated. We analytically solve the system, and by considering the eigenstate as well as the ground state as the initial state of the Floquet dynamics, we study the corresponding multiple Floquet DQPTs emerged in the micromotion with different kicking moments. The rate function of return amplitude, the Pancharatnam geometric phase and the dynamical topological order parameter are calculated, which consistently verify the emergence of Floquet DQPTs in the system.